THE DISTINCTION BETWEEN SHARIA MARKET AND CONVENTIONAL MARKET: A STUDY ON INDONESIA STOCK EXCHANGE - Nurhayadi, Yadi; Rito, Rito (Muhammadiyah University Press, 2019)
The present study investigates the differences between Islamic Economic System and Conventional Economic System that supposedly lead to the differences between sharia market and conventional market. Through bivariate and multivariate analysis, regression, correlation, and determination tests were carried out to identify the effect of conventional market on sharia market. Analysis was done based on the data of Indonesia Stock Exchange from December 2006 to May 2017, The data consisted of Jakarta Stock Exchange (JSX) Composite Index (Indeks Harga Saham Gabungan, IHSG), Jakarta Stock Exchange Liquid Index (LQ45), Jakarta Islamic Index (JII), and Indonesia Sharia Stock Index (ISSI). The results show that IHSG and LQ45 have a significant positive correlation with JII or ISSI. While IHSG and LQ45 are classified as the elements of conventional market, JII and ISSI are the representation of Sharia market. It indicates that sharia market and conventional market are both present with the same character. In other words, sharia market is still influenced by banking interest rate and speculation. To confirm this finding, the list of issuers on IDX, LQ45, JII, and ISSI was examined and the specific sharia issuers were compared with non- sharia issuers, therefore the classification of IHSG and LQ45 as conventional market is corrected. Based on the results of the analysis of regression, correlation, determination, and investigation of the collected data, a model of sharia market stability is formulated.